Dreamweavers hinabing panaginip (Makati City Bookmark Video and Moving Images, 1999)
A documentary video on the life of the T'boli of Lake Sebu. It shows how their psychic life has changed over time and how they are struggling to keep their myths and dreams alive to survive an environment that has been unfriendly and even hostile. The story will be told by the T'boli themselves, traditional weavers and performers, through their music, dance and art.
VHS format.
Director and cameraman, Fruto Corre ; concept, Raul Rodrigo ; editors, Bobby Regalado and Nonoy Regalado ; production manager, Stella Chiu.
Narrator, Pinky Amador.
Keywords: T'bolis -- Social life and customs; Hand weaving -- South Cotabato; Tnalak (Textile) -- Philippines